2016
DOI: 10.1039/c6an00035e
|View full text |Cite
|
Sign up to set email alerts
|

A tunable Au core–Ag shell nanoparticle tip for tip-enhanced spectroscopy

Abstract: A single Au nanoparticle (NP) with a diameter of 5 nm was transferred to the end of a Si-tip through a picking process, and an Ag shell with a controlled thickness was formed on the Au core. By carrying out tip-enhanced Raman scattering (TERS) measurements on biphenyl-4-thiol (BPT) with the Au@Ag NP-tip (overall diameter of 22-60 nm), we confirm that such tips show a plasmonic local-field enhancement which is sufficient for tip-enhanced spectro-microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The radius of the filaments can be as small as 3 nm. Recently, Kim and co-workers used single DNA strands to tether 5-nm Au NPs onto AFM probes and then transferred the tips into enhancing solutions to make core–shell Au–Ag NPs and Au nanostars in high yields . TERS and tip-enhanced fluorescence measurements were successfully conducted with these tips, but the low reproducibility of the geometry, such as the particle shape and orientation of spikes, resulted in a large tip-to-tip variation in enhancement factors.…”
Section: Nanoantenna Design Fabrication and Characterizationmentioning
confidence: 67%
“…The radius of the filaments can be as small as 3 nm. Recently, Kim and co-workers used single DNA strands to tether 5-nm Au NPs onto AFM probes and then transferred the tips into enhancing solutions to make core–shell Au–Ag NPs and Au nanostars in high yields . TERS and tip-enhanced fluorescence measurements were successfully conducted with these tips, but the low reproducibility of the geometry, such as the particle shape and orientation of spikes, resulted in a large tip-to-tip variation in enhancement factors.…”
Section: Nanoantenna Design Fabrication and Characterizationmentioning
confidence: 67%
“…To prevent or restrain the randomness of hot spot localization (unavoidable in metal films) and improve the manufacturing reproducibility of AFM‐TERS tips, selective decoration of tip apexes with Ag, Au, and Au–Ag core–shell NPs was performed by means of laser‐induced synthesis, dielectrophoresis, or applying the pick‐up process on dendron‐modified AFM tips followed by the growth of an Ag shell or Au spikes . Microfabrication methods (FIB milling, photolithography, …) also attracted much interest due to their ability to manufacture highly reproducible nanostructures with relatively high electromagnetic field enhancements.…”
Section: Experimental Developments In Tersmentioning
confidence: 99%
“…Groups have demonstrated fabrication of plasmonic probes by mounting Au nanoparticles onto nonplasmonic tips. ,, You et al reported using alternating current dielectrophoresis for grafting individual Ag nanowires to W wires with demonstrated TERS activity . In addition, Kim et al demonstrated in situ growth of a Ag-coated Au nanoparticle at the apex of an AFM tip . Finally, electrochemical deposition of plasmonic nanoparticles at the conductive apex of a nanoprobe enables reproducible tips whose optical properties can be tailored. , Such methods allow researchers to tailor physical properties of constructed tips, such as plasmon frequency, for particular applications.…”
Section: Tersmentioning
confidence: 99%
“…143 In addition, Kim et al demonstrated in situ growth of a Ag-coated Au nanoparticle at the apex of an AFM tip. 158 Finally, electrochemical deposition of plasmonic nanoparticles at the conductive apex of a nanoprobe enables reproducible tips whose optical properties can be tailored. 159,160 Such methods allow researchers to tailor physical properties of constructed tips, such as plasmon frequency, for particular applications.…”
Section: Tip Fabricationmentioning
confidence: 99%